INVESTIGATION OF ANTIHEMOLYTIC, XANTHINE OXIDASE INHIBITION, ANTIOXIDANT AND ANTIMICROBIAL PROPERTIES OF SALVIA VERBENACA L. AERIAL PART EXTRACTS. - Belkhiri, Farida; Baghiani, Abderrahmane; Zerroug, Mohammed Mihoub; Arrar, Lekhmici (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: In this study, Salvia verbenaca L. aerial part extracts (SVEs): were screened for their antihemolytic, xanthine oxidase (XO) inhibition, antioxidant and antimicrobial activities. Material and methods: To investigate SVEs antihemolytic activity, the 2,2,-azobis (2-amidinopropane) dihydrochloride (AAPH) was used to induce erythrocyte oxidative hemolysis. In XO inhibition test, xanthine was used as substrate and cytochrome c for generating superoxide anions. The antioxidant activity of SVEs was examined by means of reducing power, DPPH free radical scavenging and iron chelating assays. In addition, SVEs were tested for their antimicrobial effects by evaluating antibacterial and antifungal activities. Results: Ethyl acetate extract (EAE) contains the highest amount of total polyphenols and flavonoids (661.78 ± 4.00 mg GAE / g E) and (28.81 ± 0.38 mg QE / g E) respectively. In antihemolytic test EAE was the most active extract with an HT50 value of 165 min. SVEs gave significant inhibitory effects on XO, especially the chloroform extract (ChE) with IC50 value of 0.0088 ± 0.000 mg/ml. EAE was the most active extract in reducing power essay (EC50: 0.0047 ± 0.000 mg/ml) and in DPPH radical scavenging essay (IC50: 0.0086 ± 0.000 mg/ml). Finally, the EAE has inhibited the growth of nine bacterial strains with inhibition zone diameters of (12 to 16 mm), but no activities have found against fungal strains. Conclusion: S. verbenaca could be considered as a potential source of natural antihemolytic, enzyme modulator, antioxidant and antibacterial agents.